The Effects of Foreign Direct Investment on Income Inequality of Thailand - Teeramungcalanon, Monthinee; Chiu, Eric M.P. (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2020)
In the era of globalization, whether foreign direct investment (FDI) has contributed to larger income gaps is still open to debate, especially for many emerging market economies. This paper explores the effects of sectoral FDI on income inequality using panel data across the five regions of Thailand over the period of 1998–2017. We find that at the regional level, FDI in the manufacturing sector has directly contributed to reducing income inequality through employment effects and knowledge spill overs, while FDI in the agricultural sector, the manufacturing sector and the service sector have tended to lower the consumption expenditure inequality under the effects of decreasing consumption propensity. In addition, FDI in the service sector has tended to reduce absolute poverty at the aggregate level, while FDI in the agricultural sector and the anufacturing sector have contributed to increasing absolute poverty.